Depiction of Chamunda with multiple arms - Temples of India Project Team (Jio Institute, 2024)
Within the enclosure wall, there is a depiction of Chamunda, portrayed with multiple arms. Although the image has faded over time, some characteristics are still discernible. Chamunda is depicted holding a sarpa (snake) in her upper arms, a khatvanga (staff) in one hand, and a severed human head in another. Additionally, a human figure is shown to her left, attending to her.